Using handheld user interface and direct manipulation for architectural modeling in immersive virtual reality: An exploratory study - Tastan, Hasan; Tuker, Cetin; Tong, Togan (WILEY, 2022)
This study comparatively investigates the affordances and constraints of two modeling methods for three-dimensioanl modeling in immersive virtual reality (IVR): handheld user interface (HUI) and direct manipulation modeling (DM). The experimental study was conducted with 20 graduate students and two domain experts. Data were collected with screen capture videos of the modeling screen and video recordings of the users' gestures during the modeling session. To triangulate the findings for better reliability, an open-ended questionnaire was administered just after the modeling session to collect written data about the modeling experience and the investigated modeling methods. Collected data were analyzed by qualitative coding methods. Analyses focused on affordances and constraints of modeling techniques, user preferences about virtual environments, effects of instant scale feature during modeling, locomotion techniques in IVR, ergonomics of the hardware related to modeling tasks, and usability of modeling interfaces in IVR. The results showed that DM modeling could be supported by (i) numeric input via a novel type of keyboard, (ii) a convenient HUI's menu interface with menu hierarchy wherever needed, and (iii) better locomotion techniques. This study generated suggestions for ensuring that efficient modeling applications for design studios, computer aided design courses, and professional practices in IVR can be implemented by investigating affordances and constraints.
Keywords: 3D modeling; affordances; usability; virtual environment; virtual reality; PLATFORM; DESIGN; INPUT; SIZE; Computer Science; Education & Educational Research; Engineering